Ø£ÙÙÙØ§Ù Ø¹Ù Ø§ÙØ¨Ø¯ÙØ¹ : ØªØ§Ø±ÙØ®Ù ÙØ£ÙØ³Ø§ÙÙ - Faqihudin, Didin (Hunafa: Jurnal Studia Islamika, 2007)
This articleÂ  deals with one aspect of balaghah i.e. badiâ. As we know badiâ is a science by which we know some beautiful features of sentences. But howÂ  badiâ emerged in the history of Arabic culture? Who is responsible for the rising ofÂ  badiâ? And how many partsÂ  badiâ has? This articleÂ  tries to answer these questions.Â Kata Kunci : âilm al-badiâ,âilm al-balagah, âilm al-bayan,âilm al- maâani